Long non‐coding RNA expressed in macrophage co‐varies with the inflammatory phenotype during macrophage development and polarization. Issue 10 (16th August 2019) - Xie, Yixin; Wang, Min; Tian, Jingjing; Li, Xianping; Yang, Min; Zhang, Kan; Tan, Shan; Luo, Lingli; Luo, Can; Peng, Longkai; Tang, Aiguo
Abstract: Advances in microarray, RNA‐seq and omics techniques, thousands of long non‐coding RNAs (lncRNAs) with unknown functions have been discovered. LncRNAs have presented a diverse perspective on gene regulation in diverse biological processes, especially in human immune response. Macrophages participate in the whole phase of immune inflammatory response. They are able to shape their phenotype and arouse extensive functional activation after receiving physiological and pathological stimuli. Emerging studies indicated that lncRNAs participated in the gene regulatory network during complex biological processes of macrophage, including macrophage‐induced inflammatory responses. Here, we reviewed the existing knowledges of lncRNAs in the processes of macrophage development and polarization, and their roles in several different inflammatory diseases. Specifically, we focused on how lncRNAs function in macrophage, which might help to discover some potential therapeutic targets and diagnostic biomarkers.